2018
DOI: 10.1080/15476286.2018.1493328
|View full text |Cite
|
Sign up to set email alerts
|

Influence of transcriptional variants on metastasis

Abstract: Cancer metastasis is defined as the dissemination of malignant cells from the primary tumor site, leading to colonization of distant organs and the establishment of a secondary tumor. Metastasis is frequently associated with chemoresistance and is the major cause of cancer-related mortality. Metastatic cells need to acquire the ability to resist to stresses provided by different environments, such as reactive oxygen species, shear stress, hemodynamic forces, stromal composition, and immune responses, to coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 186 publications
(430 reference statements)
0
9
0
Order By: Relevance
“…Different splice variants are associated with primary tumors and metastases when compared to normal tissue. Classical examples are E-cadherin, CD44, TP53, and EGFR [50,51]. However, there is little overlap between individual splice variants and different cancer types [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different splice variants are associated with primary tumors and metastases when compared to normal tissue. Classical examples are E-cadherin, CD44, TP53, and EGFR [50,51]. However, there is little overlap between individual splice variants and different cancer types [16].…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing may affect tumor progression towards metastasis [50]. Among top differentially expressed gene variants in metastatic lesions were genes coding for CEA Cell Adhesion Molecule 1 (CEACAM1), tropomyosin 1 (TPM1), and several chemokines and chemokine receptors such as C-X-C Motif Chemokine Ligand 12 (CXCL12) and C-X-C Motif Chemokine Receptor 3 (CXCR3).…”
Section: Discussionmentioning
confidence: 99%
“…The way of expression has been suggested as a tumor progression marker (Bagnato & Rosanò, 2019). The experimental studies reported that the 2 variably expressed splicing isoforms of hMENA are present among the isoforms in breast cancer, lung cancer, and pancreatic cancer (De Faria Poloni & Bonatto, 2018). These are hMENA11a and hMENAΔv6.…”
Section: Specific Role Of β‐Arrestins Isoforms In Cancer Regulationmentioning
confidence: 99%
“…We successfully classified 40% of basal-like breast cancer patients (75/188) from the Cancer Genome Atlas (TCGA) [35] as basal Blike based on a unique 25 spliced gene signature characteristic of cells undergoing EMT. In this signature, we found well-known markers of malignancy, such as ENAH EMT splice variant that promotes lung metastasis [36] or CSF1 variant which promotes macrophage infiltration and distal metastasis [37], together with new promising splicing candidates of tumour progression and invasiveness (PLOD2, CTNND1, SPAG9). Finally, expression of this basal B signature was sufficient to identify triple negative breast cancer tumours with poor survival, highlighting the prognostic value of the newly identified splicing biomarkers to subclassify one of the most heterogenous and difficult to treat type of breast cancer.…”
Section: Introductionmentioning
confidence: 99%